Synoptic analysis of atmospheric patterns associated with pervasive frosts in Khuzestan province - zahra hejazizadeh; farshad pazhoh; fardin ghadami; haniyeh shakiba (تحقیقات کاربردی علوم جغرافیایی)
The aim of this study is to synoptic analyze of the number of frost days in a year of Khuzestan province. For this purpose, using the minimum daily temperature data of 12 stations during the statistical period of 1992 to 2017, the Meteorological Organization of the country, 54 days of frost was identified. Sea level pressure, Geopotential Height, Zonal and meridian wind and temperature of 500 hPa data with size of 2/5 * 2/5 degree arc from the National Oceanic and Atmospheric United States of America were extracted. On the matrix of the variance of sea level pressure data in 54 days, the analysis of the basic components was performed and 10 components which identified 83% variance of the sea level pressure. Then, by applying the hierarchical cluster analysis method, the integration method was applied to the scores of the 10 components and 5 patterns of sea level pressure were identified. The results showed that frost phenomenon in Khuzestan province occurs from November to march and its trend is decreasing during the statistical period. Also northern and western parts of the province have allocated the most frequency of frost. Also the synoptic condition analysis of troposphere showed that 5 sea level pressure pattern with different make ups lead to pervasive frosts of Khuzestan province. Weak and moderate frosts formed by the influence of Siberian and European cold high pressure systems. But severe frosts occur with spread of Iceland low pressure to Iran, along with strong cold pressures. Meanwhile, the powerful Siberian high pressure is present in most of the patterns, which its interaction with sub polar and Icelandic low pressure, plays the most role in the most severe frost in the province of Khuzestan. Also in the middle level of troposphere penetration of deep troughs from northern latitudes and east European huge blockings has the most role, which has advection of cold air from the side west of troughs on the country and during the intensity of the frost added to its continuity.